Detection of genomic rearrangements from targeted resequencing data in Parkinson's disease patients. Issue 1 (7th November 2016) - Spataro, Nino; Roca‐Umbert, Ana; Cervera‐Carles, Laura; Vallès, Mònica; Anglada, Roger; Pagonabarraga, Javier; Pascual‐Sedano, Berta; Campolongo, Antònia; Kulisevsky, Jaime; Casals, Ferran; Clarimón, Jordi; Bosch, Elena
ABSTRACT: Background: The analysis of coverage depth in next‐generation sequencing data allows the detection of gene dose alterations. We explore the frequency of such structural events in a Spanish cohort of sporadic PD cases. Methods: Gene dose alterations were detected with the eXome‐Hidden Markov Model (XHMM) software from depth of coverage in resequencing data available for 38 Mendelian and other risk PD loci in 394 individuals (249 cases and 145 controls) and subsequently validated by quantitative PCR. Results: We identified 10 PD patients with exon dosage alterations in PARK2, GBA‐GBAP1, and DJ1 . Additional functional variants, including 2 novel nonsense mutations (p.Arg1552Ter in LRRK2 and p.Trp90Ter in PINK1 ), were confirmed by Sanger sequencing. This combined approach disclosed the genetic cause of 12 PD cases. Conclusions: Gene dose alterations related to PD can be correctly identified from targeting resequencing data. This approach substantially improves the detection rate of cases with causal genetic alterations. © 2016 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.